RANCANG BANGUN SISTEM PENGONTROL BATCH MIXER PADA INDUSTRI MINUMAN DENGAN METODE PID BERBASIS ARDUINO UNO R3 - Hati, Redi Permata; Subari, Arkhan (Vocational School Diponegoro University, 2018)
Redi Permata Hati, Arkhan Subari, in this paper explain that batch Mixer is a tool that accommodates some of the raw materials to be mixed so that it becomes a usable product. Raw materials can be a liquid, solid and gas. The use of raw materials and way of mixing the raw materials that distinguish Batch Mixer design at each industry. In this thesis, design Batch Mixer consists of two tanks, namely the mixing tank and tank heaters. In the mixing tank, there HCSR-04 Ultrasonic sensor that functions as a detector of the level of the liquid level, and the stirrer motor-driven DC 12 V. While the heater tank, there MAX6675 Thermocouple temperature sensor and heater. There are also three pumps that pump fluid 1, pump 2 and pump fluid mixing. Batch Mixer working process is controlled automatically using the Arduino Uno R3 displayed via HMI Raspberry Pi. The use Arduino Uno R3 allows users to create a variety of issues related to the microcontroller.Â The control system is used to control the work process in a plant. The control system in the Batch Mixer works by two indicators: the water level and water temperature. In the manufacturing system, water temperature control using PID control (Proportional Integral Derivative) with PID tuning method to find the value of Kp, Kd, and Ki. Based on test results, use the most optimal value for use PID control value Kp = 60, Ki = 0.005 and Kd = 0.5. By using the value of the achievement level will be faster and the value of the maximum error of 2.5% is still within the tolerance limits of 3%.